2018
DOI: 10.24925/turjaf.v6i7.820-827.1647
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Comparison of In Vitro Radical Scavenging Activity of Both Garlic Oil and Aqueous Garlic Extracts and Their In Vivo Antioxidant Effect on Schistosomiasis Disease in Mice

Abstract: Garlic has long been utilizing as a folk remedy for various diseases. In this study, the effect of aqueous garlic extract (AGE) (125 mg kg -1 ), garlic oil extract (GOE) (125 mg kg -1 ), and the combination of both extracts (AGE+GOE) (62.5 from each) was studied over a parasitic disease namely schistosomiasis. Determination of some radical scavenging activities including Ferric Reducing Ability Power, Hydrogen peroxide, DPPH and nitric oxide radical scavenging activities were studied. The antioxidant propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…AL had a more significant effect on RBCs and HCT of the infected mice than PZQ and CU, which may be due to a reduction of worms and egg load. Consistently with this result, it was reported previously that S. mansoni infected groups treated with garlic oil or aqueous garlic extracts (or a mixture of both) showed a significant improvement in HGB and HCT in comparison with infected-untreated animals [ 19 ]. Also, CU-infected treated mice showed an increase in the values of RBCs and HCT after two weeks of treatment [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…AL had a more significant effect on RBCs and HCT of the infected mice than PZQ and CU, which may be due to a reduction of worms and egg load. Consistently with this result, it was reported previously that S. mansoni infected groups treated with garlic oil or aqueous garlic extracts (or a mixture of both) showed a significant improvement in HGB and HCT in comparison with infected-untreated animals [ 19 ]. Also, CU-infected treated mice showed an increase in the values of RBCs and HCT after two weeks of treatment [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Infected groups treated with PZQ, AL, or CU showed improvement in these parameters in comparison with infected-untreated mice. Garlic and its derivatives (as well as CU) were investigated previously as antischistosomal drugs, and they were also found to act as proper antioxidants [ 10 , 19 , 24 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have indicated that the extract of garlic shows high scavenging of free radicals and therefore has powerful antioxidant ability [ 304 , 305 ]. Furthermore, other studies have reported that garlic shows antioxidant ability including one research which analyzed this ability using in vivo experiments [ 71 , 306 ]. Amino acids such as alliin represent one of the important components of garlic [ 307 ].…”
Section: Antimicrobial Agentmentioning
confidence: 99%
“…Allicin (AL) is the main active ingredient of Allium sativum (commonly known as garlic) and is considered responsible for many of the beneficial effects associated with this plant ( 12 – 16 ). While many in vitro studies have examined the efficacy of garlic extract as an antischistosomiasis drug ( 17 , 18 ), few have studied the effects of AL in isolation ( 19 ). Curcumin (CU), the active ingredient of Curcuma longa (commonly known as turmeric) is a phenolic compound and a yellow pigment often used as a spice and food colorant ( 20 ).…”
Section: Introductionmentioning
confidence: 99%